The Traditional Classification and Treatment of Illness on Woleai and Lamotrek in the Caroline Islands, Micronesia - Alkire, William H. (Culture, 1982)
Three classes of spirits are important in the domains of illness and curing— “malevolent” spirits that cause sickness, divination spirits that diagnose ailments, and “good” spirits that aid in curing. Diviners, medicine curers, and massage curers focus on different aspects of treatment. This compartmentalization of knowledge and an associated pattern of cross-referal means that patients frequently consult with all three types of specialists. This not only maximizes the chances for cure but minimizes the possibility of assigning blame for failed cures. The organizing principles emphasized in these domains include dualistic and quadripartite divisions, lineality, locality, and homologous associations.